Correction: Cardiovascular Risk Factors and Clinical Outcomes among Patients Hospitalized with COVID-19: Findings from the World Heart Federation COVID-19 Study. Issue 1 (31st October 2022) - Prabhakaran, Dorairaj; Singh, Kavita; Kondal, Dimple; Raspail, Lana; Mohan, Bishav; Kato, Toru; Sarrafzadegan, Nizal; Talukder, Shamim Hayder; Akter, Shahin; Amin, Mohammad Robed; Goma, Fastone; Gomez-Mesa, Juan; et al.
This article details a correction to: Prabhakaran D, Singh K, Kondal D, Raspail L, Mohan B, Kato T, et al. Cardiovascular Risk Factors and Clinical Outcomes among Patients Hospitalized with COVID-19: Findings from the World Heart Federation COVID-19 Study. Global Heart . 2022; 17(1): 40. DOI:http://doi.org/10.5334/gh.1128 .